Journey - Becker, Aaron, 1974- (Somerville, Mass. : Candlewick Press, 2013)
A young girl, having escaped from her loneliness through a door she drew on her bedroom wall, is captured by an evil emperor and must find a way to escape.
School Library Journal starred, July 2013.
Booklist starred, August 2013.
Pub Weekly, May 2013.
Kirkus Starred, June 2013.
New York Times, July 2013.
Horn Book, September 2013.
Keywords: Doors -- Juvenile fiction; Drawing -- Juvenile fiction; Magic -- Juvenile fiction; Stories without words; Doors -- Fiction; Drawing -- Fiction; Magic -- Fiction; Fantasy; Fantasy fiction